190k views
1 vote
Please solve I’m confused

Please solve I’m confused-example-1
User Rson
by
5.4k points

2 Answers

4 votes

Answer:

C

Explanation:

Applying the rule of exponents


(a^m)^(n) =
a^(mn)

note that


a^(m) ×
a^(n) =
a^((m+n))

Hence


(2^3)^(1) =
2^(3(1)) =
2^(3) = 8

The classmate has mistakenly added the exponents to obtain


(2^3)^(1) =
2^((3+1)) =
2^(4) = 16 ← incorrect

User Tamir Gefen
by
5.7k points
3 votes

Answer:

A. the proper steps that should have been taking would be to first would be to raise 2 to the power of 3, which would give you 8. Then raise it to the power of 1. So the most likely error is C. they added the exponents.

User Chandan Nayak
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.